Mechanism involved in interleukin‐21‐induced phagocytosis in human monocytes and macrophages - Vallières, F. (Clin Exp Immunol, 2016)
The interleukin (IL)‐21/IL‐21 receptor (R) is a promising system to be exploited for the development of therapeutic strategies. Although the biological activities of IL‐21 and its cell signalling events have been largely studied in immunocytes, its interaction with human monocytes and macrophages have been neglected. Previously, we reported that IL‐21 enhances Fc gamma receptor (FcRγ)‐mediated phagocytosis in human monocytes and in human monocyte‐derived macrophages (HMDM) and identified Syk as a novel molecular target of IL‐21. Here, we elucidate further how IL‐21 promotes phagocytosis in these cells. Unlike its ability to enhance phagocytosis of opsonized sheep red blood cells (SRBCs), IL‐21 did not promote phagocytosis of Escherichia coli and zymosan by monocytes and did not alter the cell surface expression of CD16, CD32 and CD64. In HMDM, IL‐21 was found to enhance phagocytosis of zymosan. In addition, we found that IL‐21 activates p38, protein kinase B (Akt), signal transducer and activator of transcription (STAT)‐1 and STAT‐3 in monocytes and HMDM. Using a pharmacological approach, we demonstrate that IL‐21 enhances phagocytosis by activating some mitogen‐activated protein kinases (MAPKs) and phosphoinositide 3‐kinase (PI3K)–Akt and Janus kinase (JAK)–STAT pathways. These results obtained in human monocytes and macrophages have to be considered for a better exploitation of the IL‐21/IL‐21R system for therapeutic purposes.